ENERGY VALUE OF ELEPHANT LABOUR - Gajaseni, Jiragorn (วารสารวนศาสตร์ไทย, 2022)
Never before has anyone attempted to calculate the energy value of an elephant at work. There are several countries where the elephant still plays a significant role in the forestry industry. This study calculated the energy expended per hour by a working elephant to be 13,003. 74 kcal. In differs from assigned values for large draft animals. The working specifications for a full- grown bull elephant were also given. Even though the elephant has given way to machinery in the timber industry, it is worthwhile preserving both as a renewable from of energy and as an Exotic art form.